Reduction reactions dominate the interactions between Mg alloys and cells: Understanding the mechanisms - Jua Kim; Jeremy L. Gilbert; William W. Lv; Ping Du; Haobo Pan (Bioactive Materials)
Magnesium (Mg) alloys are popular biodegradable metals studied for orthopedic and cardiovascular applications, mainly because Mg ions are essential trace elements known to promote angiogenesis and osteogenesis. However, Mg corrosion consists of oxidation and reduction reactions that produce by-products, such as hydrogen gas, reactive oxygen species, and hydroxides. It is still unclear how all these by-products and Mg ions concomitantly alter the microenvironment and cell behaviors spatially and temporally. This study shows that Mg corrosion can enhance cell proliferation by reducing intracellular ROS. However, Mg cannot decrease ROS and promote cell proliferation in simulated inflammatory conditions, meaning the microenvironment is critical. Furthermore, cells may respond to Mg ions differently in chronic or acute alkaline pH or oxidative stress. Depending on the corrosion rate, Mg modulates HIF1α and many signaling pathways like PI3K/AKT/mTOR, mitophagy, cell cycle, and oxidative phosphorylation. Therefore, this study provides a fundamental insight into the importance of reduction reactions in Mg alloys.